“Are we there yet?”: a study of the Oxford University Press pathways to school improvement - Davis, S (2018)
This study explores the workings of, and practitioner engagement with, a selection of online resources provided by the Oxford University Press (OUP) intended to support primary schools’ engagement in improvement tasks. On 5 November 2013, the OUP launched ‘Pathways’, an online ‘four-step system’ to school improvement comprising the following phases: ‘audit’, ‘strategic planning’, ‘take action’ and ‘evaluate impact’. The resources, consisting of 23 different Pathways divided by ‘issue’, aim to support primary schools through a range of whole school improvement and curriculum-focused topics, for example increasing parental engagement and promoting outstanding reading. This research investigated primary school practitioner perceptions and attitudes towards OUP Pathways and both collective and individual improvement practice via an embedded multi-method case study comprising a purposive sample of five primary schools that signed up to use Pathways. It also followed the evolution of Pathways itself using a “design-based research” (DBR) framework. DBR focuses on bridging the realms of academia and external, more practical contexts, the documentation and monitoring of how designs function in authentic settings (The Design-Based Research Collective, 2003) and promoting research impact through user engagement in the development of theoretically-linked real-world learning environments. The growth and use of Pathways by schools was investigated through the theoretical lenses of the Dynamic Approach to School Improvement, DASI (Creemers and Kyriakides, 2012) and Guskey’s five-level model of Continuing Professional Development, CPD evaluation (2002a). During the project, teachers and school leaders engaged with a variety of resources to inform their practice and support collaborative working with colleagues, including Pathways. This research focuses uniquely on how teaching practitioners engage with and perceive technology in their school improvement practice and professional development experiences. Pathways, rather than being regarded as a digital platform on its own, appeared to function as part of a bigger ‘professional learning environment’ and ‘school improvement space’ for practitioners that enabled more structured offline and wider interactions and discussions to take place around school improvement issues. Pathways tools seemed to offer opportunities for teachers and middle leaders to work both collaboratively, individually and autonomously – with their work being partially ‘mediated’ by Pathways itself as a resource, and specific ‘hospitable conditions’ cultivated by senior leadership such as professional guidance, support and trust. The nexus of two fields that are usually studied separately is explored here: school improvement and its links with how knowledge is developed, managed and mediated; and practitioners’ use of digital technologies for their own learning and development. This study’s unique contribution to the fields of educational effectiveness and improvement and educational digital technologies lies in its innovative application of a DBR framework to study primary school improvement processes and journeys, and how these might be influenced by the development of an online technology platform for teachers that aims to extend knowledge and develop their capacities to engage in improvement practice.